A Captive, a Wreck, a Piece of Dirt: Aging Anxieties Embodied in Older People With a Death Wish. (December 2019) - van Wijngaarden, Els; Leget, Carlo; Goossensen, Anne; Pool, Robert; The, Anne-Mei
The aims of this present study were to explore the use and meaning of metaphors and images about aging in older people with a death wish and to elucidate what these metaphors and images tell us about their self-understanding and imagined feared future. Twenty-five in-depth interviews with Dutch older people with a death wish (median 82 years) were analyzed by making use of a phenomenological–hermeneutical metaphor analysis approach. We found 10 central metaphorical concepts: (a) struggle, (b) victimhood, (c) void, (d) stagnation, (e) captivity, (f) breakdown, (g) redundancy, (h) subhumanization, (i) burden, and (j) childhood. It appears that the group under research does have profound negative impressions of old age and about themselves being or becoming old. The discourse used reveals a strong sense of distance, disengagement, and nonbelonging associated with their wish to die. This study empirically supports the theory of stereotype embodiment.